PENYULUHAN DAN PELATIHAN PENANAMAN DAUN SEMBUNG RAMBAT (MAKANIA MICRANTHA) SEBAGAI TERAPI AWAL ANTI DIARE DI DESA JAPAN, MAGELANG, JAWATENGAH - Aslam, Muhammad Muzhil; Ayuningrum, Lia Dian; Fitroh, Astri Nur; Aryanti, Atiqah Fitri (Jurnal Berdaya Mandiri, 2023)
Diarrhea is a disease caused by environmental factors, knowledge factors and behavioral factors that cause changes in the volume, density and frequency of excretion of feces. The prevalence of diarrhea in Indonesia is very high, especially in children. Sembung vines (mikania micrantha) is a plant that contains secondary metabolites, one of which is a flavonoid which can be used as a medicine for diarrhea. This activity is carried out by lecture and practice methods. The purpose of community service activities is to increase knowledge about vines, their use as a medicine for diarrhea and skills in planting vines. The activity was carried out in Jetis and Prambanan Hamlets, Japan Village, Magelang, Central Java. The activity was attended by 20 Kelompok Wanita Tani . From the results of the evaluation, there was an increase in knowledge and interest in cultivating vines Keywords: Sembung Rambat leaves, therapy, anti-diarrhea